2010
DOI: 10.1007/s00167-010-1292-0
|View full text |Cite
|
Sign up to set email alerts
|

Early functional outcome after subvastus or parapatellar approach in knee arthroplasty is comparable

Abstract: PurposeIn total knee arthroplasty, tissue-sparing techniques are considered more important, as functional gain could become more advantageous when early mobilization is commenced. The parapatellar approach is most often used, whereas the subvastus approach is a suitable alternative. Presently, it is unknown, according to true objective measurements, which of the two is most advantageous.MethodsIn this prospective randomized double-blind, short-term trial measurements (KSS, WOMAC, PDI, VAS, ability to perform) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 40 publications
4
48
1
Order By: Relevance
“…However, in present study there was no statistically significant difference in blood loss in the two groups. Blood loss in the present study was much less in comparison to various other studies, 12,13 as shown in ►Table 6.…”
Section: Discussioncontrasting
confidence: 58%
“…However, in present study there was no statistically significant difference in blood loss in the two groups. Blood loss in the present study was much less in comparison to various other studies, 12,13 as shown in ►Table 6.…”
Section: Discussioncontrasting
confidence: 58%
“…One study showed that quadriceps strength was significantly better in the subvastus group in the early postoperative period, but not during long-term follow-up after TKA [63]. Another study showed no differences in knee scores in the early postoperative period, except for slightly less extension lag in the subvastus group [67]. Patellar vascularity was not compromised nor was there any difference in anterior knee pain between the subvastus and medial parapatellar approaches [68].…”
Section: Surgical Interventionsmentioning
confidence: 99%
“…Nine studies that met the inclusion criteria were included in the meta- analysis (Figure 1). 10,[14][15][16][19][20][21][22][23] Of the included trials, 8 were randomized controlled trials 10,14-16,19-22 and 1 was a quasirandomized, controlled trial (randomized by hospital number). 23 In addition, 2 quasirandomized, controlled trials (randomized by surgeon) were excluded 11,24 because the data were unavailable for meta-analysis.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…10 Several trials have compared the clinical results of the subvastus and medial parapatellar approaches in TKA, but the conclusions were conflicting. Van Hemert et al 14 and Bourke et al 15 advised not to use the subvastus approach because no significant benefits were found. However, Roysam and Oakley 10 and Sastre et al 16 recommended using the subvastus approach for TKA due to its superior clinical and func-tional results.…”
mentioning
confidence: 99%